2006
DOI: 10.1111/j.1365-3083.2006.01748.x
|View full text |Cite
|
Sign up to set email alerts
|

The Unveiling of Hidden T‐Cell Determinants of a Native Antigen by Defined Mediators of Inflammation: Implications for the Pathogenesis of Autoimmunity

Abstract: A major hypothesis for the induction of autoimmunity invokes the enhanced display of previously hidden (cryptic) epitopes under inflammatory conditions leading to the activation of self-reactive T cells. However, there is meager data that directly validate the influence of specific immune mediators on the upregulation of the presentation of cryptic determinants in vivo. We tested the effect on well-defined cryptic epitopes of hen eggwhite lysozyme (HEL) of the availability locally of a cytokine (IL-2, IL-4, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…23 Benzalkonium chloride, contained in diquafosol, is known to be degraded into hydrogen peroxide (H 2 O 2 ), 24 and can cause oxidative damage to corneal and conjunctival epithelial cells even in small amounts, as low as 0.003%. 25 It also has the potential to initiate ocular surface damage and subconjunctival inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…23 Benzalkonium chloride, contained in diquafosol, is known to be degraded into hydrogen peroxide (H 2 O 2 ), 24 and can cause oxidative damage to corneal and conjunctival epithelial cells even in small amounts, as low as 0.003%. 25 It also has the potential to initiate ocular surface damage and subconjunctival inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that self-tolerance might be infringed in autoimmunity by the activation of T cells directed against cryptic self-determinants [15], [16]: well-processed and -presented antigenic determinants are immunodominant, while poorly processed/presented ones curtail the activation of specific T cells and are thus cryptic. Then, certain conditions (e.g., addition of a cleavage site [17] or of inflammatory mediators [18]) can help circumvent self tolerance and thereby lead to autoimmunity. Viral or bacterial infections have also been suspected as triggering factors for autoimmune disorders, possibly through molecular mimicry and/or bystander activation of autoreactive cells.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In fact, tear samples from glaucoma patients have been shown to have greater amounts of infl ammatory cytokines compared to their normal counterparts. 49 Although fi brinogen is suspected as being upregulated indirectly (secondary to the infl ammatory cytokines), 50 it (ie, fi brinogen), 12 CRP, 11 and multiple cytokines, 13,14 specifi cally IL-1α and β, IL-2, IL-4, IL-6, IL-10, IL-12, IL-23, and TNFα, have long been described as conventional markers of infl ammation. used in concentrations varying from 0.015% to 0.05%, 4 although the American College of Toxicology has concluded that BAK can be safely used as an antimicrobial agent at concentrations up to 0.1%.…”
Section: 3mentioning
confidence: 99%
“…8 BAK, is known to be degraded into hydrogen peroxide (H 2 O 2 ), 8 which, in even small amounts as low as 30 parts per million (0.003%), is known to be an ophthalmic irritant. 9,10 C-reactive protein (CRP), 11 fi brinogen, 12 and multiple cytokines, 13,14 specifi cally interleukin (IL-)1α and β, IL-2, IL-4, IL-6, IL-10, IL-12, IL-23, and tumor necrosis factor (TNF-)α, have long been described as conventional biomarkers of infl ammation. Increased toxicity should cause a localized infl ammatory response with concomitant increased elaboration of these infl ammatory biomarkers.…”
Section: Epstein Chen and Asbell 416mentioning
confidence: 99%